Behind bars ; Smokey/Art for all ; City insurgency [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
Life behind prison bars. What goes on in the mind of a person behind bars; Hubert Araytn, an Austrian artist, finds that his art finds meaning in the lives of the resident of Smokey Mountain. Takes a look at insurgency problem in the City.